Isolation And Characterization Of Mesenchymal Cells From Human Bone Marrow And Their Development Into Bone Cells - Shahidan, Wan Nazatul Shima (2007)
Everyday thousands of people suffer from bone diseases that lead to destruction of bone tissue. Various types of bone allograft, xenograft and synthetic biomaterial are now used for bone replacement therapy. The future of bone reconstruction lies in the use of stem cell technology for bone development. Within the bone marrow stroma there are exists a subset of nonhematopoietic cells referred to as mesenchymal stem cells (MSCs) or mesenchymal progenitor cells (MPCs). These cells can be expanded ex vivo and induced, either in vitro or in vivo, to terminally differentiate into osteoblasts, chondrocytes, adypocytes, tenocytes, myotubes, neural cells, and hematopoietic supporting stroma. The multipotential of these cells, their easy collection and culture, as well as their high ex vivo expansive potential makes these cells an attractive therapeutic tool. The purpose of this study was to isolate, expand and characterize mesenchymal stem cell from human bone marrow in Mesenchymal Stem Cell Growth Medium (MSCGM), to compare the cell growth in the MSCGM and Dulbecco Modified Eagle‟s Medium (DMEM) with 10% Fetal Bovine Serum (FBS) medium, to differentiate MSCs into osteoblast cells and to determine the osteogenic potential of the differentiated MSC by detecting the expression of osteoblast-specific genes such as collagen type 1, osteocalcin, runx 2, osteopontin and alkaline phosphatase. In this study, MSCs were isolated from human bone marrow and cultured in MSCGM medium and DMEM-10% FBS medium. Culture-expansion of MSCs was characterized by the presence of CD 105 marker using Labelled Streptavidin Biotin (LSAB) method. The MSCs were cultured in the MSCGM and DMEM-10% FBS medium within five days. The MSCs were then cultured in osteogenic medium containing DMEM medium supplemented with Fetal Bovine Serum (FBS), antibiotics, ascorbic acid, β-glycerol phosphate and dexamethasone to differentiate into osteoblasts. Their osteogenic differentiation was determined with the formation of a mineralized extracellular matrix visualized by Von Kossa staining and Alkaline Phosphatase (ALP) assay. Moreover, osteogenic differentiation was also judge by RT-PCR profiling of osteoblast gene expression. MSC first attached to the dish surface and exhibited fibroblast-like spindle shape. The cells were also identified as MSCs based on their immunophenotype of CD 105 which resulted in funchia coloured staining. The MSCs culture in MSCGM medium expanded and proliferated rapidly compared to MSCs culture in DMEM-10% FBS medium. Incubation of bone marrow-derived MSCs in the osteogenic medium for 3 weeks resulted in a dramatic increase in ALP activity and accumulation of calcium deposit, as assessed by ALP assay and Von Kossa staining, respectively. This osteogenic potential upon culture in osteogenic medium was further confirmed by the RT-PCR analysis where the expressions of osteoblast specific genes were confirmed by molecular weight produced on agarose gel. We conclude that MSCGM is the best choice for expanding and proliferating MSCs and suggest that MSC from bone marrow have pure osteogenic potential and have the capability to differentiate into osteoblast. This potential assures that bone marrow can be a legitimate source of MSCs for production of osteoblast which can be utilized in bone replacement therapy.